2022
DOI: 10.3389/fmech.2022.979771
|View full text |Cite
|
Sign up to set email alerts
|

Meeting future NOX emissions using an electric heater in an advanced aftertreatment system

Abstract: Engine and aftertreatment solutions are being identified to meet the upcoming ultra-low NOx regulations on heavy duty vehicles as published by the California Air Resources Board (CARB) and proposed by the United States Environmental Protection Agency (US EPA) for the year 2027 and beyond. These standards will require changes to current conventional aftertreatment systems for dealing with low exhaust temperature scenarios. One approach to meeting this challenge is to supply additional heat from the engine; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The highlighted components are considered new items necessary for meeting the tight limits of the EU VII standard [74]. A recent study by Meruva et al [75] showed that a 7 kW catalyst heater can meet the ultra-low NOx 2027 regulation when combined with a closed-coupled light-off SCR. In a recent work by Sharp et al [76] from Southwest Research Institute (SwRI), the authors showed that they achieved CARB ultra-low NOx MY 2027+ limits by modifying the aftertreatment system over composite (cold and warm starts) Federal Test Procedure (FTP) and low load cycle (LLC).…”
Section: Engine Aftertreatment System (Eats)mentioning
confidence: 99%
“…The highlighted components are considered new items necessary for meeting the tight limits of the EU VII standard [74]. A recent study by Meruva et al [75] showed that a 7 kW catalyst heater can meet the ultra-low NOx 2027 regulation when combined with a closed-coupled light-off SCR. In a recent work by Sharp et al [76] from Southwest Research Institute (SwRI), the authors showed that they achieved CARB ultra-low NOx MY 2027+ limits by modifying the aftertreatment system over composite (cold and warm starts) Federal Test Procedure (FTP) and low load cycle (LLC).…”
Section: Engine Aftertreatment System (Eats)mentioning
confidence: 99%
“…Earlier, Lindemann et al [30] demonstrated an SCR warm-up time reduction of over 60% using a 10 kW EHC over the world harmonized transient cycle (WHTC). Similarly, Meruva et al [31] integrated a 7 kW EHC upstream from a close-coupled SCR followed by the main SCR system, which helped meet the CARB's 2027 NOx 0.02 g/kWhr target for HD engines. Later, EHC-integrated powertrain studies focused on optimizing the EHC power rating and SCR thermal performance.…”
Section: Introductionmentioning
confidence: 99%